Handoff ordering using signal strength for multimedia communications in wireless networks. - Ruay-Shiung Chang
In this paper, we present a method for improving the quality of service (QoS) in multimedia wireless systems based on prioritization of handover requests. A strategy called signal strength for multimedia communications (SSMC) is proposed. In this strategy, we calculate a handoff priority for every multimedia service using three values: the static priority value, the degradation rate of the received signal strength (ΔRSS), and the RSS level itself. Then, each handoff request is queued and handled according to its priority value. We present the detailed algorithm and analyze its performance on a 25-cell network. Then, its performance is compared with other methods by simulations. The results indicate our method can effectively reduce the handoff call dropping probability compared to nonpriority schemes.
Keywords: QoS; Call dropping probability; Cell network; Handoff ordering; Multimedia communications; Quality of service; Signal strength; Static priority value; Wireless networks